Asian Thought on China's Changing International Relations - Kavalski, Emilian. author. aut Link
IX, 254 p.
Keywords: At the end of the Cold War, commentators were pondering how far Western ideas would spread; today, the debate seems to be how far Chinese ideas will reach. This volume examines Chinese international relations thought and practices, identifying the extent to which China's rise has provoked fresh geo-strategic and intellectual shifts within Asia.